Comparison of Approaches for Stroke Prophylaxis in Patients with Non-Valvular Atrial Fibrillation: Network Meta-Analyses of Randomized Controlled Trials. - Navkaranbir S Bajaj; Rajat Kalra; Nirav Patel; Taimoor Hashim; Hemant Godara; Sameer Ather; Garima Arora; Tilak Pasala; Thomas T Whitfield; David C McGiffin; Mustafa I Ahmed; Steven G Lloyd; et al. (PLoS ONE)
Background Multiple novel oral anticoagulants and left atrial appendage closure devices (WATCHMAN) have been tested against dose-adjusted vitamin K antagonists in randomized controlled trials for stroke prophylaxis in non-valvular atrial fibrillation. No direct comparisons of these strategies are available from randomized controlled trials. We conducted the current analyses by combining efficacy and safety characteristics of all FDA approved stroke prophylaxis treatment strategies for patients with non-valvular atrial fibrillation. Materials and methods We searched SCOPUS from 1945 till October 2015 for randomized controlled trials comparing these strategies and reporting efficacy and safety outcomes. Six randomized controlled trials were identified and included in the final analyses and review. We followed PRISMA guidelines for network meta-analyses while reporting the current analyses. We collected data on ischemic stroke, major bleeding, and the composite primary safety endpoint as defined by various randomized controlled trials. Network meta-analyses were conducted using consistency and inconsistency models for efficacy and safety outcomes. Surface under the cumulative ranking curve were then utilized to cluster rank these treatments for safety and efficacy. Results Six randomized controlled trials with 59,627 patients comparing six treatment strategies were eligible for the analyses. All prophylaxis strategies had comparable rates of ischemic stroke. Apixaban was associated with the least number of primary safety endpoint events as compared with all other treatments. In the cluster analyses assessing safety and efficacy, apixaban, edoxaban and dabigatran ranked best followed by vitamin K antagonists and rivaroxaban, whereas the WATCHMAN left atrial appendage closure device ranked last. Conclusions Dose-adjusted vitamin K antagonists, novel oral anticoagulants, and the WATCHMAN left atrial appendage closure devices are equally efficacious for ischemic stroke prevention but these treatments have different safety profiles. More randomized controlled trials are needed to directly compare these strategies.